Rockabilly riot! [compact disc] : all original - Setzer, Brian (Surfdog, 2014)
Three-time Grammy Award winner Brian Setzer delivers a straightforward blast of pure rockabilly with twelve original and high-octane tracks. His first studio album since 2011 also includes the single Let's Shake.